Pendampingan Perancangan Fasilitas Pendukung Wisata Desa di Kapanewon Sedayu Kabupaten Bantul - Amos Setiadi; Gerarda Orbita Ida Cahyandari; Fabiola Chrisma Kirana Analisa; Augustinus Madyana Putra; Emy Wahyuningtyas; Cisyulia Octavia (PELITA NUSA TENGGARA, 2026)
The Kapanewon Sedayu tourist village plays a significant role in improving the local community's economic conditions. The problem is that the supporting infrastructure and physical facilities are not yet available and are essential elements. This Community Service project aims to design a physical infrastructure to support tourist comfort. The design approach emphasizes the development of supporting facilities and infrastructure for tourism activities, with community leaders participating in the site survey. The results of the activity are the designs of four architectural objects: a welcome gate, a parking area, a post, and a tubing pier to support community-based, environmentally conscious river-traveling nature tourism. The supporting facilities are expected to strengthen the branding of the Kapanewon Sedayu. This Community Service (PPM) activity uses observation methods and a design approach that combines the potential of natural resources and handicrafts, involving local communities as tour guides, tourism entrepreneurs, and workers in the tourism sector. Thus, village tourism development not only provides economic benefits but also improves residents' welfare.